Hak Kewarganegaraan dalam Konstitusi Indonesia dan Prinsip Dzimmah dalam Hukum Islam - Defana Tri Rakhiish Dani; M. Fahmi Fahruddin; M. Rizki Prasertyo; Abdul Roja (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Every individual possesses both rights and obligations that must be understood and exercised in a balanced manner to maintain social order, justice, and collective well-being. A clear understanding of citizens’ responsibilities is essential for creating a prosperous and harmonious society. This study examines the rights and obligations of citizens as stipulated in the 1945 Constitution of the Republic of Indonesia, with a primary focus on exploring how the Constitution guarantees, regulates, and implements these fundamental principles in national life. The research employs a qualitative method with a descriptive-analytical approach. Data were collected through desk research, analysis of constitutional provisions, examination of relevant legal documents, and review of related academic literature. The findings indicate that the 1945 Constitution provides strong protection for fundamental human rights, including the rights to education, health services, employment, legal protection, and freedom of expression. At the same time, the Constitution clearly outlines citizens’ obligations, such as obeying the law, paying taxes, respecting the rights of others, participating in national defense, and contributing to social harmony. The study emphasizes that rights and obligations are interconnected and must be carried out proportionally. Understanding and applying these constitutional principles is crucial for strengthening democratic governance, enhancing legal awareness, and fostering a just, orderly, and sovereign nation.